Fe (II) + HCI→ AI + HCI→

Mg + H2SO4 →

K + H2SO4 →

AI + H2SO4 →

Mg+ H3PO4→

K+ H3PO4→

AI + H3PO4→​

strunets1 strunets1    3   08.01.2021 17:16    4

Ответы
Arinka722 Arinka722  07.02.2021 17:18

Fe (II) + 2HCI→ FeCl2 + H2

2AI + 6HCI→ 2AlCl3 + 3H2

Mg + H2SO4 → MgSO4 + H2

2K + H2SO4 → K2SO4 + H2

2AI + 3H2SO4 → Al2(SO4)3 + 3H2

3Mg+ 2H3PO4→ Mg3(PO4)2 + 3H2

6K+ 2H3PO4→ 2K3PO4 + 3H2

2AI + 2H3PO4→ 2AlPO4 + 3H2

ПОКАЗАТЬ ОТВЕТЫ
llallallup llallallup  07.02.2021 17:18

Объяснение:

Fe + 2HCl = FeCl2 + H2

2Al + 6HCl =2 AlCl3 + 3H2

Mg + H2SO4 = MgSO4 + H2

2K + H2SO4 = K2SO4 + H2

2Al + 3H2SO4 = Al2(SO4)3 + 3H2

3Mg + 2H3PO4 = Mg3(PO4)2 + 3H2

6K + 2H3PO4 = 2K3PO4 + 3H2

2Al + 2H3PO4 = 2AlPO4 + 3H2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Химия